2012
DOI: 10.1177/1358863x12436708
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of different methods to measure the endothelial function

Abstract: This study compares the reliability and reproducibility of flow-mediated dilatation (FMD) and peripheral arterial tonometry (PAT) to assess endothelial function. Eighteen volunteers with coronary heart disease underwent simultaneous testing of FMD by means of brachial artery ultrasound scanning and PAT with the EndoPAT 2000. The subjects underwent both tests twice with an interval of 30 minutes and the same protocol was repeated 2 days later. The within-day variability was lower for the FMD measurements than f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
77
3
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 23 publications
(23 reference statements)
14
77
3
3
Order By: Relevance
“…The software then calculated the augmentation index (AI), a measure of arterial stiffness and reactive hyperemia index (RHI), a measure of nitric oxide mediated endothelial vasodilation. Prior studies suggest that a 10% level of day-to-day test variability is expected (9). Both elevated AI and diminished RHI suggest vascular and endothelial disease.…”
Section: Methodsmentioning
confidence: 99%
“…The software then calculated the augmentation index (AI), a measure of arterial stiffness and reactive hyperemia index (RHI), a measure of nitric oxide mediated endothelial vasodilation. Prior studies suggest that a 10% level of day-to-day test variability is expected (9). Both elevated AI and diminished RHI suggest vascular and endothelial disease.…”
Section: Methodsmentioning
confidence: 99%
“…Onkelinx et al 20 showed that the within-day variability was lower with FMD than for PAT, while between-day variability was similar in a…”
Section: Limitationsmentioning
confidence: 99%
“…Therefore, discrepant results are conceivable. Although Endo-PAT and FMD correlate well in healthy subjects [135], in patients with chest pain [136] and with coronary artery disease [137] such comparisons between the two techniques in both healthy and obese children are still missing. Pubertal development and its associated hormonal changes complicate the study of endothelial function in children.…”
Section: Peripheral Arterial Tonometrymentioning
confidence: 99%